2018
DOI: 10.3892/ijmm.2018.3747
|View full text |Cite
|
Sign up to set email alerts
|

GDF‑15 prevents LPS and D‑galactosamine‑induced inflammation and acute liver injury in mice

Abstract: Growth differentiation factor‑15 (GDF‑15) is a transforming growth factor (TGF)‑β superfamily member with a poorly characterized biological activity, speculated to be implicated in several diseases. The present study aimed to determine whether GDF‑15 participates in sepsis‑induced acute liver injury in mice. Lipopolysaccharide (LPS) and D‑galactosamine (D‑GalN) were administered to mice to induce acute liver injury. Survival of mice, histological changes in liver tissue, and levels of inflammatory biomarkers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…GDF15 is upregulated in many tissues in response to inflammation and may reduce the activation of proinflammatory factors, consequently inhibiting the activation of nuclear factor-κB. 26 The activation of mTORC1 by aging or pathological conditions may increase the expression of GDF15 and STAT3's phosphorylation in skeletal muscles, which could then induce oxidative stress and catabolic changes in skeletal muscle. 27 GDF15 has also been implicated in mitochondrial dysfunction, which may play an essential role in muscle dysfunction through the loss of ATP (adenosine triphosphate) production, reduced oxidative phosphorylation, deregulation of the ubiquitin-proteasome pathway, decrease in mitochondrial biogenesis, endoplasmic reticulum stress, mitophagy, modification of mitochondrial DNA and increased mitochondrial oxidative stress in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…GDF15 is upregulated in many tissues in response to inflammation and may reduce the activation of proinflammatory factors, consequently inhibiting the activation of nuclear factor-κB. 26 The activation of mTORC1 by aging or pathological conditions may increase the expression of GDF15 and STAT3's phosphorylation in skeletal muscles, which could then induce oxidative stress and catabolic changes in skeletal muscle. 27 GDF15 has also been implicated in mitochondrial dysfunction, which may play an essential role in muscle dysfunction through the loss of ATP (adenosine triphosphate) production, reduced oxidative phosphorylation, deregulation of the ubiquitin-proteasome pathway, decrease in mitochondrial biogenesis, endoplasmic reticulum stress, mitophagy, modification of mitochondrial DNA and increased mitochondrial oxidative stress in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also showed that IH inhibited hepatocyte apoptosis and autophagy induced by inflammation, thereby improving liver function [20]. It indicated that the hepatoprotective role of IH could be attributed to the anti-inflammation effect [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Though the data above have demonstrated the pivotal role of TNF-α in aGVHD-mediated BM damage, the molecular mechanisms underlying TNF-α control of the stemness and hematopoiesis-promoting capacity of MSCs need to be further clarified. In the current study, the comprehensive results of a high-throughput RNA sequencing analysis suggested that numerous genes including ICAM-1, IL-1β, BMP4, and GDF15 may be responsible for the special mechanisms of TNF-α mediated effects of stem cell properties [34][35][36][37][38]. The further GO annotation revealed the biological process of the differential abundant genes.…”
Section: Discussionmentioning
confidence: 60%